Two-Dimensional Generalization of the Rutishauser qd -Algorithm - Dmytryshyn, R. I. (Journal of mathematical sciences (New York, N.Y.), 2015)
A two-dimensional generalization of the Rutishauser qd -algorithm is proposed. The conditions of existence of this algorithm are established. Some examples of analytic functions represented by regular two-dimensional C -fractions with independent variables are given.